Conditions influencing the change of defense budgets - the case of Lithuania - Gediminas Dubauskas (Insights into Regional Development)
During the so-called Cold War the financing of the defense budget was widely discussed. The issue of financing the defense budget was widely discussed during the arms race. Since the end of the Cold War, armed conflicts have become more complex, and their causes are even more diverse than during the Cold War. They were caused by the deterioration of inter-ethnic divisions, hybrid and cyber wars over energy resources and the activities of terrorist groups. Due to the changing security dimension, a new study was conducted examining the determinants of defense spending in a changing security environment: the creation of new islands in the South China Sea to expand China’s military-political power in the region; the possibility of using North Korea's nuclear energy. weapons, Russia’s military maneuver in the conflict in Ukraine, its naval operation in the Black Sea, the occupation of Crimea, military operations in Syria, a change in U.S. military doctrine. The state that has spent the most military spending is returning to the creation of large military units, and to do so, the country needs to increase defense spending. Looking at how these world events work, we see one component that connects them. Strong force, expressed in military action, is used to achieve their political goals. Military power is gaining more and more influence in the formation of foreign policy, therefore the defense budget, as an instrument of foreign policy expressed in military power, is becoming an increasingly relevant object of research. Lithuania's defense budget is not as important to world politics as the United States, China or other major countries in the world, but it is relevant and significant in its region. Expenditures on the Lithuanian military budget began to increase significantly by two thousand and fourteen. It can be argued that the factor that has now influenced cost growth is Russia’s military aggression in Ukraine. Nevertheless, in 2008 Russia's aggression in Georgia did not affect the growth of Lithuania's defense budget. 2008 The economic crisis may have influenced Lithuania's decision not to increase military spending. Some pressure on the country's defense budget is also related to the 2020 Pandemic crisis. The question arises as to why seemingly similar conflicts affect Lithuanian political decisions differently.